Gymnastics Jitters - Jake Maddox (Stone Arch Books, 2012)
Dana and the rest of the Raiders gymnastics team must learn how to deal with their biggest rivals, the Superiors. When the Superiors don't play fair, the Raiders learn a valuable lesson in sportsmanship.
Keywords: Sport Stories -- Sport Stories